Response of Pole Type French Bean (Phaseolus vulgaris L.) Genotypes to Sowing Dates in the Mid Hills of Western Nepal - Pandey, YR; Gautam, DM; Thapa, RB; Sharma, MD; Paudyal, KP (Nepal Journal of Science and Technology, 2013)
Three pole-type French bean (Phaseolus vulgaris L.) genotypes (Four season, Trishuli & Makwanpur) were sown in different three dates, i.e., August 16, 31 and September 15 during autumn seasons of 2010 and 2011 at the Agriculture Research Station, Malepatan, Pokhara (848 msl) to assess the fresh pod yield and yield attributes of the genotypes in different dates of sowing. The experiment was conducted in randomized complete block design with three replications. The temperature ranged from 14° to 32°C during the growth period. The results showed significant variations in fresh pod yield and yield attributes. Flowering was earlier in Makwanpur genotype. About 50% plants flowered within 39 days in Makwanpur while it took more than 48 days for Trishuli. Tallest plants were produced by Makwanpur (271.7 cm) and shortest by Trishuli (256.2 cm). The pod length was highest (18.34 cm) in Four season and lowest in Makwanpur (15.07 cm). Pod width was highest in Trishuli (9.04 mm) and lowest in Makwanpur (7.10 mm). Highest fresh pod yield was produced by Four season (25.08 t/ha) followed by Makwanpur (23.11t/ha) and the lowest by Trishuli (19.97 t/ha). Sowing date also showed significant effect on yield and yield attributes. Earliest sowing (16 August) showed better results in early flowering (42.63 days), tallest plants (280.4 cm), longest pods (18.51 cm), widest pods (9.21 mm) and the highest fresh pod yield (31.13 t/ha) than 31 August and 15 September sown conditions. Fresh pod yield was highest in 16 August sown (31.13 t/ha) followed by 31 August (21.74 t/ha) and lowest in 15 September (15.29 t/ha). Four season sown on 16 August produced the highest fresh pod yield with an average of 35.35 t/ha. The result revealed that Four season is the best genotype and mid August is the appropriate sowing time for higher fresh pod yield of French bean in the mid hills of western Nepal. Nepal Journal of Science and Technology Vol. 13, No. 2 (2012) 15-20 DOI: http://dx.doi.org/10.3126/njst.v13i2.7708